PAQR3 Regulates Endoplasmic Reticulum-to-Golgi Trafficking of COPII Vesicle via Interaction with Sec13/Sec31 Coat Proteins - Cao, Qianqian; Wang, Zheng; Wan, Huida; Xu, Lijiao; You, Xue; Liao, Lujian; Chen, Yan (iScience, 2018)
Endoplasmic reticulum (ER)-to-Golgi anterograde transport is driven by COPII vesicles mainly composed of a Sec23/Sec24 inner shell and a Sec13/Sec31 outer cage. How COPII vesicles are tethered to the Golgi is not completely understood. We demonstrated here that PAQR3 can facilitate tethering of COPII vesicles to the Golgi. Proximity labeling using PAQR3 fused with APEX2 identified that many proteins involved in intracellular transport are in close proximity to PAQR3. ER-to-Golgi trafficking of N-acetylgalactosaminyltransferase-2 on removal of brefeldin A is delayed by PAQR3 deletion. RUSH assay also revealed that ER-to-Golgi trafficking is affected by PAQR3. The N-terminal end of PAQR3 can interact with the WD domains of Sec13 and Sec31A. PAQR3 enhances Golgi localization of Sec13 and Sec31A. Furthermore, PAQR3 is localized in the ERGIC and cis-Golgi structures, the acceptor sites for COPII vesicles. Taken together, our study uncovers a role for PAQR3 as a player in regulating ER-to-Golgi transport of COPII vesicles.